Effect of Presence or Absence of Corpus Luteum on Ovarian Dimensions, Number of Follicles and the Quality of oocytes in Local Cows (Bos Indicus) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The present study was aimed to assessing the influence of presence or absence of corpus luteum (CL) on the dimensions of ovaries and the number of follicles and oocytes and their quality in local cows. A total of 256 cow ovaries were collected from abattoirs of Babylonian province for the period from September 2017 until April 2018. The female reproductive system were transported to the laboratory within 2 hour post slaughter. The ovaries were removed and categorize into 2 groups based on the presence (n=150) or absence (n=106) of CL. The ovaries were measured their dimensions, and the follicle were counted, measured and classified according to their diameter as small 3-5 (mm) , medium 6-9 (mm) and large 10-20 (mm). The follicular fluid were aspirated and the oocyte were collected, examined , measured , evaluated, and graded. The result of present study showed a significant higher (P